SAT0475 Recent onset psoriatic arthritis: baseline data from the reapser study. (15th June 2017) - Queiro, R; Alonso, A Laiz; Park, HS; Morales, C Montilla; Agirregoikoa, E Galíndez; Baute, JJ Bethencourt; Reyes, S Bustabad; Tejόn, P Menéndez; Belmonte, MΆ; Tasende, JA Pinto; Morales, EA Blanco; Ramír, J
Abstract : Background: The natural history of psoriatic arthritis (PsA) is very little known and the information regarding prospective cohorts is very scarce worldwide, including our country. REAPSER (Spanish Rheumatology Society Registry of Psoriatic Arthritis) is the first registry of Spanish patients with recent onset PsA. Objectives: To describe the baseline characteristics of patients included in the REAPSER cohort. Methods: Observational, multicentric study (34 centers), with consecutive inclusion. We included adults of both sexes 18 years of age or older with PsA that met CASPAR criteria, and duration of less than two years since the appearance of symptoms attributed to PsA. Annual follow-up visits will be carried out for 5 years. Measurements: socio-demographic data; employment status and impact of the disease; family history of PsA and other inflammatory diseases; comorbidities and treatment; lifestyle; use of health services; clinical status at the time of diagnosis of PsA; anthropometric data; clinical evaluation of PsA manifestations; radiographic evaluation; analytical determinations; treatment of PsA. The study has been approved by the ethical committees of the participating centers. Results: Two hundred and fifteen consecutive patients were included, mean age 49.8±13.9 years. Values are expressed as percentages, means with standard deviation and medians with their IQR (interquartile range). SDU: Standard Drink Units. PsAID: Psoriatic Arthritis Impact of Disease. Conclusions: The baseline situation of Spanish patients with newly diagnosed PsA corresponds to that of a disease with slight cutaneous involvement and predominance of oligoarticular arthritis. Unsurprisingly, structural damage is scarce but not zero. The impact of the disease is still low in these early stages, however 18% of patients have a high Charlson's comorbidity index (>3) and almost 5% of patients have had to change their employment status in the last year due to its PsA. Disclosure of Interest: None declared